Jellicoe Road - Marchetta, Melina, 1965- (New York : HarperTeen, 2008)
Abandoned by her drug-addicted mother at the age of eleven, high school student Taylor Markham struggles with her identity and family history at a boarding school in Australia.
Previously published in 2006 in Australia under title: On the Jellicoe Road.
Michael L. Printz Award, 2009.
Keywords: Abandoned children -- Juvenile fiction; Emotional problems -- Juvenile fiction; Boarding schools -- Juvenile fiction; Schools -- Juvenile fiction; Identity -- Juvenile fiction; Australia -- Juvenile fiction